Problematika Keabsahan Jual Beli Tanah di Bawah Tangan Tanah di Kawasan Transmigrasi - Asta Tri Setiawan; Sri Kistiyah; Rofiq Laksamana (Sekolah Tinggi Pertanahan Nasional, 2021)
Legal action regarding the purchase of land, regulated in Article 37 paragraph (1) of Government Regulation Number 24 of 1997 concerning Land Registration, stipulates that any land sale and purchase agreement must be proven by Land Titles Registration Officer (PPAT). However the communities in Harapan Jaya Village do not use the sale and purchase agreement made by Land Registration Officer (PPAT) for their land transactions, especially transmigration lands. The practice of land transactions is better known as land sale and purchase unformal. The purpose of this research is find out the causative factors of land transaction unformal, the validity of the purchase of the land and the registration of ownership rights after the land right transfer in the Land Office which not proven by Land Titles Registration Officer (PPAT). The results of research are Harapan Jaya Village prefer the land sale and purchase unformal because of the low cost and the easy process. Beside that the lack of knowledge about land transactions and the high level of mutual trust that occurs in the community. The sale and purchase of land unformal is legal according to custom law but does not fulfill the legal requirements of the agreement in Article 1320 of the Civil Code. For the registration of the transfer of land rights, The Head of the Land Office makes a discretion or policy addressing these problems by looking at the provisions in Article 37 paragraph (2) of Government Regulation Number 24 of 1997.Perbuatan hukum mengenai jual beli tanah, diatur dalam Pasal 37 ayat (1) Peraturan Pemerintah Nomor 24 Tahun 1997 tentang Pendaftaran Tanah menentukan bahwa setiap perjanjian jual beli tanah harus dibuktikan dengan akta yang dibuat oleh Pejabat Pembuat Akta Tanah (PPAT). Masyarakat di Desa Harapan Jaya dalam transaksi jual beli hak atas tanah khususnya tanah transmigrasi tidak menggunakan akta jual beli yang dibuat oleh PPAT. Praktik jual beli tanah tersebut lebih dikenal dengan istilah jual beli tanah di bawah tangan. Tujuan penelitian mengetahui faktor penyebab terjadinya jual beli tanah di bawah tangan, bagaimana keabsahan jual beli tanah tersebut dan bagaimana pendaftaran peralihan hak milik atas tanah di Kantor Pertanahan yang dibuktikan dengan akta yang tidak dibuat oleh PPAT. Hasil penelitian jual beli hak atas tanah hak milik dibawah tangan di Desa Harapan Jaya dikarenakan biayanya tidak terlalu banyak dan prosesnya sangat mudah, selain itu minimnya pengetahuan tentang tata cara jual beli tanah serta masih tingginya rasa saling percaya yang terjadi di masyarakat. Jual beli tersebut sah menurut hukum adat namun tidak memenuhi syarat sah perjanjian dalam Pasal 1320 KUH Perdata. Dalam rangka pendaftaran peralihan hak atas tanah tersebut Kepala Kantor Pertanahan membuat sebuah diskresi atau kebijakan menyikapi permasalahan tersebut dengan melihat ketentuan dalam Pasal 37 ayat (2) Peraturan Pemerintah Nomor 24 Tahun 1997.